The OceanMAPS v4 sea-ice forecast demonstration project mk 2 ... - Allen, Stewart C. R.; Brassington, Gary B.; Sakov, Pavel; Lieser, Jan L.; Beggs, Helen; Beckett, Duan; Fiedler, Russell (Zenodo, 2023)
Presentation given at the IICWG 11th International Workshop on Sea Ice Modelling, Assimilation, Observations, Predictions and Verification, 21-23 March 2023 in Oslo, Norway ...